2018
DOI: 10.1158/0008-5472.can-17-2011
|View full text |Cite
|
Sign up to set email alerts
|

CD163 Is Required for Protumoral Activation of Macrophages in Human and Murine Sarcoma

Abstract: Recent findings have shown the significance of CD163-positive macrophages in tumor progression, yet there have been few studies on the function of CD163 in macrophages. Here, we uncover the role of CD163 in macrophage activation using CD163-deficient mice and human samples. We detected CD163 in 62 undifferentiated pleomorphic sarcoma samples, in which a high percentage of CD163-positive macrophages was associated with decreased overall survival and higher histologic grade. We observed macrophage-induced tumor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 44 publications
1
73
0
Order By: Relevance
“…Therefore, immunosuppression in soft tissue sarcomas may be as a result of the action of CD163+ macrophages and may represent the reason why the efficacy of PD‐1‐targeting therapy is limited . Moreover, Shiraishi et al indicated that CD163 is related to protumoral activation of macrophages, and development and progression of tumor by interleukin‐6 from macrophages. Meanwhile, it was reported that tumor‐associated macrophages, especially CD163+ CD204+, expressed higher levels of PD‐L1 than other macrophage subsets .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, immunosuppression in soft tissue sarcomas may be as a result of the action of CD163+ macrophages and may represent the reason why the efficacy of PD‐1‐targeting therapy is limited . Moreover, Shiraishi et al indicated that CD163 is related to protumoral activation of macrophages, and development and progression of tumor by interleukin‐6 from macrophages. Meanwhile, it was reported that tumor‐associated macrophages, especially CD163+ CD204+, expressed higher levels of PD‐L1 than other macrophage subsets .…”
Section: Discussionmentioning
confidence: 99%
“…As macrophages play a crucial role in host defense, homeostasis, and erythropoiesis, non-specific depletion of TAMs may be harmful [106]. The scavenging receptor CD163, a marker of M2 macrophages and TAMs, has been shown to promote their pro-tumor activities in mice and humans [107,108].…”
Section: Strategies To Deplete Tamsmentioning
confidence: 99%
“…We also recently reported that the expression of CD163 on macrophages is associated with poor prognosis in undifferentiated human pleomorphic sarcoma. CD163 promotes murine sarcoma progression by inducing IL-6 secretion (Shiraishi et al, 2018), which indicates the pro-tumorigenic role of TAMs expressing CD163 in sarcoma. In the present study, we demonstrated that four flavonoid compounds isolated from Epimedii Herba inhibited M2 marker expression (CD163 and IL-10) in HMDMs (Figures 4A,C), while having no cytotoxic effect on these cells ( Figure 4B).…”
Section: Discussionmentioning
confidence: 93%
“…It is known that the excessive activation of STAT3 in tumor cells is associated with poor prognosis, and IL-6, a classic STAT3-activator produced by mesenchymal stem cells, induces STAT3 activation in tumor cells such as Saos-2 osteosarcoma cells and consequently promotes tumor proliferation and metastasis (Tu et al, 2012). It was recently reported that CD163-positive macrophages are also associated with both proliferation in Saos-2 cells and tumor progression in a sarcoma-bearing mouse model by IL-6-induced STAT3 activation (Shiraishi et al, 2018). Epimedokoreanin B showed an inhibitory effect on STAT3 activation in both macrophages and tumor cells ( Figures 4D, 5C,D), and epimedokoreanin B suppressed tumor progression in the LM8 tumor-bearing mouse model in the present study ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%